KEKERASAN TERHADAP ORANG TUA DALAM RUMAH TANGGA YANG DILAKUKAN ANAK KANDUNG DITINJAU DARI HUKUM ISLAM DAN UNDANG-UNDANG NO 23 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Alisyah, Salsa Chintya; Ahmad, Muh. Jufri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Domestic violence (KDRT) is a criminal act that must be carried out at the investigation level to prove that a child is a victim of violence against parents who have experienced or actually experienced the violence. This research is a normative legal research. The research approach uses a statute approach and a conceptual approach. The results of this study are in Law Number 23 of 2004 it is expressly stated that in article 5 is an act that results in fear, loss of self-confidence, loss of ability to act, feeling helpless, and/or severe suffering to family members. In this case, there was domestic violence by children against their parents which resulted in depression and physical injury. The causes of violence against biological parents by their own biological children are caused by family economic factors, social environment where they live, low education of perpetrators and lack of religious education. With the teachings of Islam strictly prohibits the occurrence of domestic violence. This is evidenced by the many verses in the Qur’an and hadith that command children to respect both people well